Zfp580 Regulates Paracrine and Endocrine Igf1 and Igfbp3 Differently in the Brain and Blood After a Murine Stroke - Hoffmann, Christian J.; Kuffner, Melanie T. C.; Lips, Janet; Lorenz, Stephanie; Endres, Matthias; Harms, Christoph (Frontiers in Physiology, 2022)
Insulin-like growth factor 1 (Igf1) and insulin-like growth factor binding protein 3 (Igfbp3) are endocrine and paracrine factors that influence stroke occurrence, severity, and recovery. Low levels of endocrine Igf1 and Igfbp3 were associated with larger infarct volumes and unfavorable outcomes. Paracrine Igf1 is brain cytoprotective and improves functional recovery after stroke. In this study, we evaluated the effects of zinc finger protein 580 (Zfp580) on endocrine and paracrine Igf1 and Igfbp3 after stroke. Zfp580 suppressed the expression of Igf1 and Igfbp3 in cerebral microvascular endothelial cells (bEnd.3) as determined by real-time RT-PCR. Zfp580 was suppressed by combined oxygen and glucose deprivation (OGD) and mediated the effect of OGD on Igf1 and Igfbp3. In vivo, we evaluated paracrine regulation by real-time RT-PCR of brain lysates and endocrine regulation by ELISA of blood samples. Genomic ablation of Zfp580 did not alter basal paracrine or endocrine Igf1 and Igfbp3 levels. After transient middle cerebral artery occlusion (MCAo), Zfp580 was globally elevated in the brain for up to 3 days. Paracrine Igf1 and Igfbp3 were selectively induced in the ischemic hemisphere from day 2 to day 3 or day 1 to day 7, respectively. In Zfp580 knockout mice, the paracrine regulations of Igf1 and Igfbp3 were attenuated while endocrine Igf1 and the molar Igf1/Igfbp3 ratio were increased. In conclusion, Zfp580 differentially controls paracrine and endocrine Igf1 and Igfbp3 after stroke. Inhibition of Zfp580 might be a new treatment target leading to increased activity of Igf1 to improve stroke outcome.